Current Situation for Pharmacists in Japanese Veterinary Medicine: Exploring the Pharmaceutical Needs and Challenges of Veterinary Staff to Facilitate Collaborative Veterinary Care - Taisuke Konno; Hiroyuki Suzuki; Naoto Suzuki; Kouji Okada; Yosuke Nishikawa; Daisuke Kikuchi; Hitoshi Nakamura; Yuriko Murai (Pharmacy)
While veterinary pharmacy is common overseas, it has yet to gain traction in Japan. To clarify the actual situation in Japan, two surveys were conducted, targeting 4017 facilities (2000 pharmacies/drug stores, 2000 veterinary medical facilities, and 17 university-affiliated veterinary hospitals). We received 324 responses from pharmacy staff and 217 from veterinary hospital staff. Pharmacists were involved in drug therapy for companion animals either via direct discussion with veterinarians or by referrals for prescriptions from veterinarians (11 respondents). Veterinary staff and pharmacists showed a disparity regarding pharmacists’ involvement in companion animal healthcare. Veterinary staff wanted pharmacists to provide pharmaceutical guidance, perform audits, supply drug information, and prepare drugs. Strong demand (72.2% of the veterinary staff) existed for consultations with pharmacists regarding medication issues. Veterinary medicine has evolved to meet the demand for the advanced care of companion animals. Veterinary staff have diverse and substantial requests for pharmacists. Integrating the expertise of both veterinary staff and pharmacists may facilitate a team-based approach to veterinary medicine and improve the quality of care for companion animals. Tailoring approaches to suit Japan’s unique circumstances and creating a conducive environment for effective communication between pharmacists and veterinary staff are pivotal for advancing veterinary pharmacy in Japan.